Unveiling Indonesia's New Capital: A Digital Content Analysis of Tourism Narratives - Tabuni, Gasper; Singgalen, Yerik Afrianto (Journal of Information System and Informatics, 2024)
This research investigates the role of digital narratives in promoting emerging destinations, with a focus on Indonesia's new capital (IKN). Utilizing the Digital Content Reviews and Analysis Framework, this study analyzed 248 digital posts, including social media posts and videos, to evaluate the effectiveness of tourism strategies that emphasize authentic cultural elements and unique regional attractions. The findings demonstrate that strategically crafted digital content significantly increases public awareness and interest in IKN. The analysis of 194 posts, through sentiment classification and toxicity scoring, reveals a predominantly positive public discourse, with an average toxicity score of 0.05541 and a maximum score of 0.90611. The sentiment classification model exhibited high accuracy (97.46% ± 3.00%) and precision (96.78% ± 4.17%), with a micro-average accuracy of 97.48%, and a notable AUC score of up to 0.999, indicating robust differentiation between positive and negative sentiments. These results underscore the practical implications of leveraging digital media to enhance tourism promotion strategies, suggesting that effective digital narratives, supported by comprehensive analytical frameworks and minimal toxicity, are crucial for converting interest into actual tourism activity. This approach positions IKN as a competitive entity in the global tourism market, emphasizing the importance of digital narratives in shaping international perceptions of new destinations.